Simulação numérica do efeito hidrodinâmico na corrosão em acidentes de linhas de tubulações - Santos, Cecília Mageski Madeira (2012)
The impact of particles in internal wall of flow components, such as tubes, connections, valves and pumps results in increased corrosion due to the continuous removal of the protective layers of corrosion, and to the erosion of the base material, especially in the parts that the flow is projected. The hydrodynamic behavior in corrosive fluid flow is an important phenomenon for various applications of industries. In this case, the limiting factor is the presence of dissolved oxygen in the solution and the transfer of oxygen to the surface on effects of corrosion. The Computational Fluid Dynamics (CFD) can be used to compute this diffusion of oxygen in the stream and its transfer to the surface reaction. This paper presents the results of simulations via CFD for hydrodynamic behavior of a fluid after a expansion as well as oxygen diffusion in the flow and transfer of oxygen to the surface in order to estimate the mass loss from the pipe surface, using two models turbulent flow (Modelo RNG k − ε e SST k − ω) in contraction-expansion geometry. The simulations were validated after using the experimental work present in the literature.